PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI ADMINISTRASI PADA RUMAH SAKIT UMUM DAERAH DOKTER SOEDARSO - B31109106, Doni Kusnadi (Jurnal Manajemen Update, 2016)
This research was conducted in order to determine the effect of motivation and discipline on the performance of the administrative staff at the Regional General Hospital doctor Soedarso. The population in this study were employees of Regional General Hospital doctor Soedarso totaling 160 people. This type of research is a survey research. Total sample of 60 employees. Tools of this research is multiple linear regression. Based on the analysis found that the variables of motivation and discipline significant positive effect on employee performance Regional General Hospital doctor Soedarso. The independent variables (motivation and discipline) otherwise be able to explain the variance of the dependent variable (employee performance) so that the model used in this study could explain and predict or model fit for use. Statistical calculations show that discipline variables turned out to have a value greater influence than the motivation variable in affecting both the poor performance of employees Regional General Hospital doctor Soedarso. Keywords: Motivation, Discipline,Â  Performance